Analysis of Verb Tenses in Broken Memories Album: Types, Frequency, and Narrative Function - Rahayu, Siti; Nadjmuddin, Muhammad; Sunani (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
ABSTRACT: This study aims to analyze verb tense usage in the lyrics of Jamie Miller’s Broken Memories album, with three primary objectives: to classify the types of tenses used, quantify their frequency to identify temporal patterns, and examine their function in narrative construction through Labov’s (2008) pre-construction framework. Adopting a qualitative approach, this research analyzed lyrics obtained through triangulated sources, including Genius.com and official streaming platforms, and cross-referenced them with auditory verification. The data were processed using computational tagging and thematic coding to identify grammatical patterns. Findings reveal that the simple past tense dominates, often reflecting personal memories and emotional retrospection, while the present tense establishes immediacy and intimacy. The occasional use of the future tense suggests uncertainty and aspiration. These tense patterns support emotional storytelling and reflect mental narrative structuring by songwriters. The study concludes that grammar in popular music operates beyond conventional rules, functioning as a creative tool for emotional expression and audience engagement. Future research is encouraged to explore broader datasets across artists, as well as include modality, voice, and listener reception to deepen understanding of grammatical strategies in musical narratives. Keywords: Verb Tenses, Frequency, Narrative Function, Broken Memories, Pre-Construction Framework